"Flu-Floppers": Factors Influencing Families' Fickle Flu Vaccination Patterns. (May 2020) - Fogel, Benjamin N.; Hicks, Steven D.
While influenza vaccination in the prior year is a strong predictor of subsequent vaccination, many families do not have static vaccination patterns. This study examined factors guiding influenza vaccination decisions among parents whose children sporadically received the influenza vaccination (flu-floppers). We administered surveys to 141 flu-flopper families. Surveys included 21 factors associated with vaccine decision making. A conceptual framework of "passive" and "active" decision making was used to assess parental motivators behind vaccine decisions. The most common reason for vaccinating was a desire to prevent influenza (45%). The most common reason for not vaccinating was a belief that influenza vaccination is not effective (29%). Most parents (88%) reported an active reason in years when their child was vaccinated, while only 43% reported an active reason when their child was not vaccinated ( P < .00001). These findings may guide efforts to increase influenza vaccination rates in children most amenable to vaccination.